2015
DOI: 10.1093/hmg/ddv404
|View full text |Cite
|
Sign up to set email alerts
|

Neuronopathic Gaucher disease: dysregulated mRNAs and miRNAs in brain pathogenesis and effects of pharmacologic chaperone treatment in a mouse model

Abstract: Defective lysosomal acid β-glucosidase (GCase) in Gaucher disease causes accumulation of glucosylceramide (GC) and glucosylsphingosine (GS) that distress cellular functions. To study novel pathological mechanisms in neuronopathic Gaucher disease (nGD), a mouse model (4L;C*), an analogue to subacute human nGD, was investigated for global profiles of differentially expressed brain mRNAs (DEGs) and miRNAs (DEmiRs). 4L;C* mice displayed accumulation of GC and GS, activated microglial cells, reduced number of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 70 publications
2
48
1
Order By: Relevance
“…Indeed most efforts to develop a pharmacological chaperone useful in clinical practice were concentrated on Gaucher disease (Figure 2). Isofagomine, an unmodified iminosugar, appeared to be very promising in stabilizing mutant glucosylceramidase [62] but did not reduce the accumulation of lipids significantly [14,63]. Besides the approaches already mentioned with alkylated or pH-sensitive molecules, another interesting option was evaluated.…”
Section: Pharmacological Chaperones: Improvement Of a Drugmentioning
confidence: 99%
“…Indeed most efforts to develop a pharmacological chaperone useful in clinical practice were concentrated on Gaucher disease (Figure 2). Isofagomine, an unmodified iminosugar, appeared to be very promising in stabilizing mutant glucosylceramidase [62] but did not reduce the accumulation of lipids significantly [14,63]. Besides the approaches already mentioned with alkylated or pH-sensitive molecules, another interesting option was evaluated.…”
Section: Pharmacological Chaperones: Improvement Of a Drugmentioning
confidence: 99%
“…Samples analyzed include lymphocytes or serum (Karatas et al 2013;L ie ta l .2014a, b;Martino et al 2015) and fibroblasts (Ozsait et al 2010;Siebert et al 2014). In other studies, mouse (Dasgupta et al 2015) or cellular models, such as knockdown cell lines or mitochondrial cybrids, have been analyzed (Meseguer et al 2015). The identified dysregulated miRNAs and/or their mRNA targets were analyzed in silico to gain insight into their contribution to disease pathogenesis.…”
Section: Mirnas In Inherited Metabolic Diseasesmentioning
confidence: 99%
“…Thus, in Niemann-Pick C, miRNA screening identified downregulated miRNAs targeting lipid metabolism genes (Ozsait et al 2010). In Gaucher mouse model brain, differentially expressed miRNAs and target mRNAs involved in inflammatory processes, mitochondrial function, and axon guidance were described (Dasgupta et al 2015). In familial Fan et al 2016) hypercholesterolemic children, miR-33a and miR-33b were found significantly upregulated in plasma, correlating with levels of total cholesterol, low-density lipoprotein (LDL)-cholesterol, apoB, C-reactive protein, and glycemia (Martino et al 2015).…”
Section: Mirnas In Inherited Metabolic Diseasesmentioning
confidence: 99%
“…On the other hand, in a PC12 cell model transfected with WT or mutant GBA1 and over-expressing α-syn, treatment of isofagomine did not significantly reduce α-syn accumulation (95). Treatment of a mouse model representative of neuronopathic GD suggested that isofagomine treatment might restore altered expression levels of miRNA and associated mRNA in processes such as inflammation, axonal guidance pathways, and mitochondrial dysfuntion which are all implicated in PD (108). In another study, patient fibroblasts homozygous for L444P treated with the sp 2 -iminosugars based inhibitory chaperone NAdBT-AIJ revealed amelioration of mitochondrial dysfunction (109).…”
Section: Expert Review and Five-year Viewmentioning
confidence: 99%